Molecular diversity of the base-promoted reaction of phenacylmalononitriles with dialkyl but-2-ynedioates - Zheng, Hui; Han, Ying; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2022)
In the presence of tetrabutylammonium bromide (TBAB), the cycloaddition reaction of phenacylmalononitriles with dialkyl but-2-ynedioates in acetonitrile at room temperature resulted in 3,3-dicyano-5-hydroxy-5-arylcyclopent-1-ene-1,2-dicarboxylates in high yields. More importantly, the DABCO-promoted domino reaction of two molecules of each phenacylmalononitrile and dialkyl but-2-ynedioate in acetonitrile at room temperature afforded unique multifunctionalized carboxamide-bridged dicyclopentenes in moderate to good yields and with high diastereoselectivity.
Keywords: carboxamide; cycloaddition; cyclopentene; electron-deficient alkyne; phenacylmalononitrile

(untitled) - Liu, H.; Qi, C.; Wang, L.; Guo, Y.; Li, D.; Jiang, H. (J. Org. Chem., 2021)

(untitled) - Zhao, G.; Zhang, Q.; Zhou, H. (J. Org. Chem., 2014)

(untitled) - Li, M.-B.; Li, H.; Wang, J.; Liu, C.-R.; Tian, S.-K. (Chem. Commun., 2013)

(untitled) - Fedoseev, S. V.; Ershov, O. V.; Belikov, M. Y.; Lipin, K. V.; Bardasov, I. N.; Nasakin, O. E.; Tafeenko, V. A. (Tetrahedron Lett., 2013)

(untitled) - Omar, M. A.; Shaker, Y. M.; Galal, S. A.; Ali, M. M.; Kerwin, S. M.; Li, J.; Tokuda, H.; Ramadan, R. A.; El Diwani, H. I. (Bioorg. Med. Chem., 2012)

(untitled) - Lin, B.; Kou, J.; Xiao, Q.; Wu, S.; Hu, J.; Li, J.; Zhu, Z.; Zhou, X.; Xin, L.; Li, Y.; Wang, Z. (Tetrahedron, 2022)

(untitled) - Yavari, I.; Khaledian, O. (Synthesis, 2020)

(untitled) - Li, Z.-H.; Jiang, Z.-J.; Shao, Q.-L.; Qin, J.-J.; Shu, Q.-F.; Lu, W.-H.; Su, W.-K. (J. Org. Chem., 2018)

(untitled) - Ievlev, M. Yu.; Ershov, O. V.; Belikov, M. Yu.; Milovidova, A. G.; Tafeenko, V. A.; Nasakin, O. E. (Beilstein J. Org. Chem., 2016)

(untitled) - Ievlev, M. Y.; Ershov, O. V.; Tafeenko, V. A. (Org. Lett., 2016)

(untitled) - Wahl, J. M.; Pöthig, A.; Bach, T. (Org. Lett., 2016)

(untitled) - Belikov, M. Y.; Fedoseev, S. V.; Ievlev, M. Y.; Ershov, O. V.; Tafeenko, V. A. (RSC Adv., 2015)

(untitled) - Belikov, M. Y.; Ershov, O. V.; Eremkin, A. V.; Nasakin, O. E.; Tafeenko, V. A.; Nurieva, E. V. (Tetrahedron Lett., 2011)

(untitled) - Martins, C.; Eleutério, A.; Carreiras, M. C.; Samadi, A.; Soriano, E.; Léon, R.; Marco-Contelles, J. (Mol. Diversity, 2009)

(untitled) - Padmaja, A.; Payani, T.; Reddy, G. D.; Padmavathi, V. (Eur. J. Med. Chem., 2009)

(untitled) - Al-Mousawi, S. M.; Moustafa, M. S.; Meier, H.; Kolshorn, H.; Elnagdi, M. H. (Molecules, 2009)

(untitled) - Ahadi, S.; Naghdiani, Z.; Balalaie, S.; Rominger, F. (Tetrahedron, 2015)

(untitled) - Sun, J.; Yang, R.-Y.; Yan, C.-G. (ChemistrySelect, 2017)

(untitled) - Wang, Z.; Chen, W.; Luo, H.; He, C.; Zhang, G.; Yu, Y. (Synthesis, 2020)

(untitled) - Uchikura, T.; Moriyama, K.; Toda, M.; Mouri, T.; Ibáñez, I.; Akiyama, T. (Chem. Commun., 2019)

(untitled) - Li, L.; Guo, S.; Wang, Q.; Zhu, J. (Org. Lett., 2019)

(untitled) - Fu, N.; Shen, Y.; Allen, A. R.; Song, L.; Ozaki, A.; Lin, S. (ACS Catal., 2019)

(untitled) - Chen, J.; Li, C.; Zhou, Y.; Sun, C.; Sun, T. (ChemCatChem, 2019)

(untitled) - Ievlev, M. Y.; Ershov, O. V.; Milovidova, A. G.; Belikov, M. Y.; Vasil’ev, A. N.; Tafeenko, V. A. (Russ. J. Org. Chem., 2018)

(untitled) - Rakshit, A.; Kumar, P.; Alam, T.; Dhara, H.; Patel, B. K. (J. Org. Chem., 2020)

(untitled) - Sahoo, A. K.; Rakshit, A.; Dahiya, A.; Pan, A.; Patel, B. K. (Org. Lett., 2022)

(untitled) - Li, S.; Yang, W.; Luo, X.; Yao, C. (Chin. J. Org. Chem., 2019)

(untitled) - Abdelhamid, A. A.; Salama, K. S. M.; Elsayed, A. M.; Gad, M. A.; Ali Ali El-Remaily, M. A. E. A. (ACS Omega, 2022)

(untitled) - Elsayed, A. M.; El‐Remaily, M. A. E. A. A. A.; Salama, K. S. M.; Abdelhamid, A. A. (J. Heterocycl. Chem., 2022)

(untitled) - Adib, M.; Sheikhi, E.; Haghshenas, P.; Bijanzadeh, H. R. (Synlett, 2010)

(untitled) - Alishetty, S.; Shih, H.-P.; Han, C.-C. (Org. Lett., 2018)

(untitled) - Chen, C.; Wei, R.; Yi, X.; Gao, L.; Zhang, M.; Liu, H.; Li, Q.; Song, H.; Ban, S. (J. Org. Chem., 2019)

(untitled) - Vaishanv, N. K.; Chandrasekharan, S. P.; Zaheer, M. K.; Kant, R.; Mohanan, K. (Chem. Commun., 2020)

(untitled) - Gao, L.; Li, G.; Li, X.; Zhang, G.; Zhang, M.; Li, Q.; Ban, S. (Org. Chem. Front., 2022)

(untitled) - Han, Y.; Guo, L.-Y.; Yan, C.-G. (Heterocycl. Commun., 2015)

(untitled) - Han, Y.; Tang, W.-Q.; Guo, L.-Y.; Yan, C.-G. (Tetrahedron, 2014)

(untitled) - Yang, F.; Zhang, L.-J.; Yan, C.-G. (RSC Adv., 2014)

(untitled) - Sun, J.; Chen, L.; Gong, H.; Yan, C.-G. (Org. Biomol. Chem., 2015)

(untitled) - Zhang, J.; Sun, J.; Yan, C.-G. (RSC Adv., 2015)

(untitled) - Chen, L.; Sun, J.; Xie, J.; Yan, C.-G. (Org. Biomol. Chem., 2016)

(untitled) - Zhang, Y.; Sun, J.; Shen, G.-L.; Yan, C.-G. (Org. Biomol. Chem., 2017)

(untitled) - Sun, J.; Jiang, W.; Yan, C.-G. (RSC Adv., 2018)

(untitled) - Jiang, W.; Sun, J.; Yan, C.-G. (New J. Chem., 2020)

(untitled) - Xu, F.-S.; Yan, C.; Sun, J.; Yan, C.-G. (New J. Chem., 2021)

(untitled) - Sun, J.; Xia, E.-Y.; Wu, Q.; Yan, C.-G. (Org. Lett., 2010)

(untitled) - Sun, J.; Sun, Y.; Gong, H.; Xie, Y.-J.; Yan, C.-G. (Org. Lett., 2012)

(untitled) - Han, Y.; Sheng, Y.-J.; Yan, C.-G. (Org. Lett., 2014)

(untitled) - Gao, H.; Sun, J.; Yan, C.-G. (J. Org. Chem., 2014)

(untitled) - Cao, J.; Yang, F.; Sun, J.; Huang, Y.; Yan, C.-G. (J. Org. Chem., 2019)

(untitled) - Liu, D.; Sun, J.; Xie, J.; Shi, H.; Yan, C.-G. (J. Org. Chem., 2021)